2020
DOI: 10.1029/2020rg000700
|View full text |Cite
|
Sign up to set email alerts
|

Monsoons, ITCZs, and the Concept of the Global Monsoon

Abstract: Earth's tropical and subtropical rainbands, such as Intertropical Convergence Zones (ITCZs) and monsoons, are complex systems, governed by both large-scale constraints on the atmospheric general circulation and regional interactions with continents and orography, and coupled to the ocean. Monsoons have historically been considered as regional large-scale sea breeze circulations, driven by land-sea contrast. More recently, a perspective has emerged of a global monsoon, a global-scale solstitial mode that domina… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 321 publications
(518 reference statements)
0
56
0
Order By: Relevance
“…However, even for the net cloud feedback, some regions exhibit less consistency, like India, western Pacific Ocean, North Atlantic Ocean, and high-latitude oceans. The different warming pattern in Indian and Pacific Ocean between amip4K and coupled experiments might lead to different cloud feedbacks over India because monsoon simulation is very sensitive to the air-sea coupling and land-sea temperature contrast (Endo et al, 2018;Geen et al, 2020;Singh et al, 2019;Wang, 2005). A "warming hole" is commonly simulated by coupled models in the North Atlantic (Chemke et al, 2020;Drijfhout et al, 2012;Josey et al, 2018), which could cause a locally different cloud feedback compared to that occurring when SSTs are warmed uniformly.…”
Section: Spatial Distributionmentioning
confidence: 99%
“…However, even for the net cloud feedback, some regions exhibit less consistency, like India, western Pacific Ocean, North Atlantic Ocean, and high-latitude oceans. The different warming pattern in Indian and Pacific Ocean between amip4K and coupled experiments might lead to different cloud feedbacks over India because monsoon simulation is very sensitive to the air-sea coupling and land-sea temperature contrast (Endo et al, 2018;Geen et al, 2020;Singh et al, 2019;Wang, 2005). A "warming hole" is commonly simulated by coupled models in the North Atlantic (Chemke et al, 2020;Drijfhout et al, 2012;Josey et al, 2018), which could cause a locally different cloud feedback compared to that occurring when SSTs are warmed uniformly.…”
Section: Spatial Distributionmentioning
confidence: 99%
“…Figure 4 illustrates the consequences of seasonal changes in the Hadley circulation (today), in terms of (zonal mean) rainfall distribution; the convective rainfall belt is confined to a narrow belt over oceanic regions and varies little throughout the year, whereas over continental areas where large seasonal changes in surface heating occur, heavy amounts of summer rainfall extend far from the equatorial ITCZ (Figure 5). Regions with large seasonal changes in rainfall are commonly described as having a monsoon rainfall regime (Gadgil, 2018;Geen et al, 2020). Regional variations due to the distribution of the continents and seasonal changes in circulation create sharp boundaries (geographically and temporally) between areas with a high (convective) rainfall climate regime, and much drier areas where warm, subsiding air is dominant.…”
Section: Tablementioning
confidence: 99%
“…Geophys.). This work examined the onset of the monsoon, starting from aquaplanet simulations and adding increasingly realistic orography (Geen et al 2018). Important questions relating to the poleward migration of the monsoon and the dynamical feedbacks that control the observed sharp poleward jump in the seasonal transition of the monsoon have been addressed (Geen et al 2019) where tropical moist static energy (MSE) buildup is identified as a key precursor to monsoon onset.…”
Section: Climate Dynamics and Predictabilitymentioning
confidence: 99%